Rancang Bangun Wastafel Multifungsi Untuk Tempat Perlindungan Hewan Fie Fie Jo - Soewono, Arka Dwinanda; Darmawan, Marten; Hutagalung, Rory Anthony; Gunawan, Harjadi; Fernandi; Yuwana, Vincent (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2023)
Fie Fie Joe animal shelter employees and visitors often physically contact animals while feeding, playing with, or cleaning animals and their cages. In order to prevent virus and bacteria transmission, animal shelters require everyone to wash their hands after visiting the outdoor area. The Fie Fie Jo shelter, however, faced two main problems. First, only one hand-washing station is available in their facility, allowing possible viruses or bacteria to be transmitted through physical contact with other people or objects before entering the indoor facility. Second, their staff took a long time to bathe the animals in their enclosures since there was no washing station in the outdoor area. Therefore, this outreach program aims to design and build a multi-purpose washing station for the outdoor area that can be operated by a foot pedal so that users do not need to touch the faucet physically. The washing station has additional features such as a large tub that can also be used for bathing animals, a tissue holder, and a garbage disposal to help make it easier and faster to bathe several animals simultaneously. The method used during the outreach program includes conducting a survey, performing a design process, and demonstrating how to use and maintain the multi-purpose washing station. To assess the success of this program, the Fie Fie Jo owner and employees were asked to fill out a questionnaire. The results showed that they were more than satisfied with the demonstration and performance of the washing station. The presence of the multi-purpose washing station can improve productivity and reduce the risk of viruses and bacterial contamination of the Fie Fie Joe animal shelter employees and visitors.